Treatment of a large radicular cyst - enucleation or decompression? - Matijević Stevo; Jovičić Bojan; Bubalo Marija; Dukić Smiljka; Čutović Tatjana (Vojnosanitetski Pregled)
Introduction. Radicular cysts treatment involves surgical approach, more or less aggressive. However, treatment of large cystic lesions, including radicular cysts, causes some of dilemmas concerning the choice of the surgical method, especially the degree of radicalism. Case report. We presented a 65-year-old male patient with large radicular cyst in the mandible. A large elliptical multilocular radiolucency, located in the left side of the mandible, being in close vicinity to the mandibular canal, was registered at the orthopantomographic radiography. There was a risk of pathological fracture of the mandible. However, the cyst was completely removed by enucleation without intraoperative and postoperative complications. Conclusion. The presented case support the opinion that careful enucleation of large mandibular cysts may be done without complications, such as damages of surrounding anatomical structures or mandibular fracture. The authors indicate reasons for strong support of the undertaken surgical approach of treating large radicular cysts in the mandible.